Combined ozone and ultrasound as pretreatment in the control of the pharmaceuticals and membrane fouling in membrane bioreactors - Prado, Moriel L.
The need for more sophisticated wastewater treatment processes is imperative to better degrade the contaminants including its by-products prior to discharge to aquatic environment or reuse. The sophistication of using Advanced Oxidation Processes (AOPs) enables to destroy the recalcitrant, toxic and non-biodegradable emerging compounds in wastewater that cannot be treated by conventional biological processes. Two of the known AOPs, ozonation and sonolysis, have shown synergistic effects when used simultaneously and demonstrated to have a better efficacy than used in single treatment. Likewise, they are known for their high versatility and environmental compatibility for degradation of biorefractory pollutants . In addition, their conversion to readily biodegradable intermediates can be subsequently treated and further reduce the toxicity from wastewater. Thus, this study aimed to assess the impacts of the combine ozone and ultrasound (03/US) pretreatment on the performance of a membrane bioreactor (MBR) in the removal of the different pharmaceutical compounds in simulated wastewaters, namely: diclofenac, sulfamethoxazole and carbamazepine. The impacts of the 03/US pretreatment to the process parameters, fouling and biological toxicity of the wastewater in the MBR were also assessed. Findings have shown that employing the combined process of 03/US as pretreatment to MBR was effective in fouling control due to its effects on the microbial metabolism products in the MBR. It also achieved 50% reduction of the extracellular polymeric substance (EPS) concentration. Consequently, the improvement in the operating conditions brought about appreciable removal rates of 80-84% for pharmaceuticals in the MBR effluent. On the other hand, the results of the toxicity tests have demonstrated that the O3/US treatment when applied alone did not promote significant toxicity removal of wastewater. This may be attributed to the intermediate products that have been formed during the O3/US treatment. However, there was 80% reduction of the toxicity potential in the MBR permeate indicating that these intermediate products were biologically oxidized by MBR.